EU labour migration since enlargement. Trends, impacts and policies (Aldershot, 2009)
"Focusing on labour movements in Latvia, Hungary, Poland, Austria, Germany, Sweden and the United Kingdom, this book examines the experiences and characteristics of these countries in the run up to, and particularly since, EU accession in May 2004 when full access to the labour market was suspended at the discretion of the new member states. A team of national labour economists and migration experts provide an overview of the economic and labour market dynamics faced by EU member states. They also analyze and present data on the numbers of workers that have moved, along with their characteristics and the effects on the labour markets they have joined - as well as those they have left. Separate contributions by policy experts detail the responses by governments, employers and trade unions in the countries of origin and destination, examining whether or not the challenges raised by the movement of labour have been met."